Internationella normers transformation: Responsibility to Protect och dess roll i global konflikthantering - Lazovic,Luka (2025)
The purpose of this paper is to examine an international norm, R2P, which is designed to ensure the security of civilians and protect them from atrocities such as genocide and war crimes when a state can no longer fulfill this responsibility. This paper will analyze the development, dissemination, and application of the norm through an examination of interventions in Libya and Syria. It will use the lens of social constructivism theory, highlighting how R2P has been institutionalized since its inception and whether its selective application and ties to power structures have affected the legitimacy of the norm. The findings indicate that the 2011 intervention in Libya represented a success in terms of implementing the norm. However, it was simultaneously marred by selectivity and hidden agendas. In contrast, the Syrian crisis of 2011 revealed the norm’s limitations in contexts where the international community remains divided. This paper argues that R2P has the potential to play a more significant role in international relations, but it is at risk of being undermined by inconsistencies and selective application, which diminish its potential impact. Strengthening R2P’s relevance and credibility requires measures to ensure more equitable and consistent implementation while addressing underlying power imbalances.
Keywords: Responsibility to Protect; Internationella normer; global styrning; humanitär intervention; Libyen; Syrien; Normkonflikter